Validation of a brief stigma-by-association scale for use with HIV/AIDS-affected youth in South Africa - Boyes, Mark; Mason, S.; Cluver, L. (Routledge, 2013)
This study validated a brief stigma-by-association scale for use with South African youth (adapted from the HIV Stigma-by-Association Scale for Adolescents). Participants were 723 youth (364 male, 359 female) from poor urban communities around Cape Town. Youths completed the brief stigma-by-association scale and measures of bullying victimisation and peer-problems, as well as inventories measuring symptoms of depression and anxiety. Exploratory analyses revealed that the scale consists of two subscales: (1) experience of stigma-by-association and (2) consequences of stigma-by-association. This two factor structure was obtained in the full sample and both the HIV/AIDS-affected and unaffected subgroups. The full stigma-by-association scale showed excellent reliability (α = 0.89–0.90) and reliabilities for both subscales were also good (α = 0.78–0.87). As predicted, children living in HIV/AIDS-affected households obtained significantly higher stigma-by-association scores than children in non-affected households [F(1, 693) = 46.53, p<0.001, partial η 2=0.06] and hypothesized correlations between stigma-by-association, bullying, peer problems, depression and anxiety symptoms were observed. It is concluded that the brief stigma-by-association scale is a reliable and valid instrument for use with South African youth; however, further confirmatory research regarding the structure of the scale is required.